2009
DOI: 10.17239/l1esll-2009.09.04.03
|View full text |Cite
|
Sign up to set email alerts
|

On the development of textual competence in primary education

Abstract: Abstract. The aim of this article is to present the results of an action research project, which has been put into practice in Primary Education. This project was intended to develop students' textual competence, considering both comprehension and textual production. Our starting hypothesis was that teaching the schematisation of text types, focusing on linguistic devices that underlie text production, would promote the development of textual competence, leading to the production of more coherent and cohesive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the United States, for example, the National Assessment of Educational Progress (NAEP) pointed out that one-fifth of the students in Grades 8 and 12 scored below the basic level in writing, whereas only 27% of the students performed at or above the proficient level (Graham, 2013; National Center for Education Statistics, 2012). Likewise, in the United Kingdom many primary school students scored below the expected level for writing (Ofsted, 2005), whereas in Portugal more than half of the Grade 4 students were found to be poor writers (Cardoso, Pereira, Silva, & Sousa, 2009). Similarly, a large-scale assessment in Germany on language competencies of 9th-graders found that one-third of the students wrote unacceptable texts (Klieme, 2006; Neumann, 2012).…”
mentioning
confidence: 99%
“…In the United States, for example, the National Assessment of Educational Progress (NAEP) pointed out that one-fifth of the students in Grades 8 and 12 scored below the basic level in writing, whereas only 27% of the students performed at or above the proficient level (Graham, 2013; National Center for Education Statistics, 2012). Likewise, in the United Kingdom many primary school students scored below the expected level for writing (Ofsted, 2005), whereas in Portugal more than half of the Grade 4 students were found to be poor writers (Cardoso, Pereira, Silva, & Sousa, 2009). Similarly, a large-scale assessment in Germany on language competencies of 9th-graders found that one-third of the students wrote unacceptable texts (Klieme, 2006; Neumann, 2012).…”
mentioning
confidence: 99%